Prevalensi dan Faktor Resiko Kawin Berulang pada Sapi Perah pada Tingkat Peternak (PREVALENCE AND RISK FACTORS OF REPEAT BREEDING IN DAIRY COWS AT THE FARMER LEVEL) - Prihatno, Surya Agus; Kusumawati, Asmarani; Karja, Ni Wayan Kurniani; Sumiarto, Bambang (Jurnal Veteriner, 2013)
Repeat breeding is a syndrome which affected the reproduction and production efficacy of dairy cattle.The cause of this syndrome may be a herd problem or a variety of individual cow problems. This studyaimed to determine the prevalence and factors which contributed in the repeat breeding syndrome in dairycattle farms in Daerah Istimewa Yogyakarta (DIY). A total of 922 dairy cows which owned by 401 farmerswere used in this study. The cows had a normal estrus cycle, have had at least once calved, age 2.5-8 yearsold, in good health condition, raised traditionally by a farmer or communal system. Multistage and clustersampling method were used in this study. The total numbers of sample at each stage was determined by proportional, whereas the total numbers of farmer was determined using “sampel rambang” Data werecollected by interviewing farmers and direct observation at the farm. Data collected were farmer’s education,length of having farm, farm condition, distance from inseminator, farmer’s ability to detect estrus andestrus cycle, the farm and cow’s hygiene. Data were analyzed by descriptive statistics then followed by ChiSquare and Odds Ratio. The results showed that the prevalence of repeat breeder at the dairy farms was29.4%. Risk factors at the herd level were the most common i.e.: estrus detection once per-day (OR = 17.8);estrus detection twice per-day (OR = 7.9); unsightly sewer (OR = 10.0); soil floor of enclosure (OR = 2.6); andthe use of wells or rivers as source of water (OR = 2.0 and OR = 1.8, respectively.
Keywords: repeat breeder, dairy cows, prevalence, odds ratio